Penerapan Metode Eksperimen untuk Meningkatkan Hasil Belajar Siswa Pada Materi Pesawat Sederhana Kelas V SD - Rohayati, Rohayati (Universitas Sebelas Maret, 2020)
The problem of this research is the students' learning outcomes in the science subject of simple aircraft for class V SD Negeri Citepus 01 in the 2015/2016 academic year. The purpose of this study is to improve student learning outcomes. This research was conducted in 2 cycles consisting of planning, implementation, observation and reflection. The subjects of this study were the fifth grade students of SD Negeri Citepus 01, totaling 35 students. The technique of collecting the results of the short and descriptive test results. Data analysis was carried out by analyzing quantitatively and qualitatively, to find out whether or not student learning was complete or not. Based on the learning outcomes from the pre-cycle, cycle I and cycle II experienced a significant increase. In the pre-cycle learning outcomes were 43% and increased in the first cycle by 69%, while the second cycle increased even more, namely learning outcomes reached 91%. The conclusion of this study is that the application of the experimental method can improve the learning outcomes of fifth graders at SDN Citepus 01 in science subjects about simple machines